2023
DOI: 10.1088/1755-1315/1158/2/022035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Soil Organic Carbon Content in Different Soils on Water Holding Capacity and Soil Health

Abstract: An experiment was carried out to study the effect of soil organic carbon (SOC) and soil texture on the distance of the wetting front, cumulative water infiltration (I), infiltration rate (IR), saturated water conductivity (Ks), and water holding capacity (WHC). Three levels ( 0, 10, 20, and 30 g OC kg-1 ) from organic carbon (OC) were mixed with different soil materials sandy, loam, and clay texture soils. Field capacity (FC) and permanent wilting point (PWP) were estimated. Soil materials were placed in trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Soil properties affect the ecosystem structure and function of wetlands. Studies have found that the soil's water-holding capacity increases with higher levels of organic carbon content (Masood and Ali 2023;Wang et al 2020). In contrast, sand has a weaker water-holding capacity than clay, making it easier for water to penetrate and difficult to form a wetland (Herawati et al 2021;Riaz and Marschner 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Soil properties affect the ecosystem structure and function of wetlands. Studies have found that the soil's water-holding capacity increases with higher levels of organic carbon content (Masood and Ali 2023;Wang et al 2020). In contrast, sand has a weaker water-holding capacity than clay, making it easier for water to penetrate and difficult to form a wetland (Herawati et al 2021;Riaz and Marschner 2020).…”
Section: Introductionmentioning
confidence: 99%